SEPARATION AND DETERMINATION OF THE R-ISOMER OF ETODOLAC IN A BULK DRUG SUBSTANCE BY NORMAL-PHASE LIQUID CHROMATOGRAPHY - Lawande, Appasaheb B (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the this work is to develop and validate a novel, simple,rapid and reliable analytical method for separation and determination of R-isomer impurity in Etodolac bulk drug material by normal-phase high-performance liquid chromatography as per International Conference on Harmonization guidelines. Methods: The Etodolac R- isomer and S-isomer were separated on a Chiralcel OD-H (150 x 4.0 mm, 5 micron) column by using Ethanol : n-Hexane:Trifluoroacetic acid (50:50:0.1 v/v.) mobile phase with equipped detector at wavelength 225 nm and 25 °C column oven temperature. The resolution between R-isomer and S-isomer were more than two recorded on chromatogram. The specified method was developed and validated for various parameters like reproducibility, limit of detection, limit of quantification, linearity and range, robustness, solution stability and mobile phase stability according to the International Conference on Harmonization (ICH) guidelines. Results: Linearity were found for Etodolac R-isomer over the concentration range of 600–6000 ng/ml, with the linear regression (Correlation coefficient R = 0.998) and proved to be robust. Limit of detection and limit of quantification of Etodolac R-isomer was found to be 200 and 600 ng/ml. The retention time of R-isomer was considered to be 2.8 min. The percentage recovery of Etodolac R-isomer has been ranged from 97.0 to 102.0 in bulk drug material sample. The proposed analytical method has been found to be suitable, precise,reliable and accurate for the separation and quantitative determination of Etodolac R-isomer in bulk drug sample. Conclusion: A novel, speedy, accurate, precise, reliable and rugged analytical method has been developed and validated for normal phase high performance liquid chromatography to determine R-isomer impurity in Etodolac bulk drugs material as per ICH guideline. Keywords: Etodolac, HPLC, Known Impurity. Normal Phase, Validation.